The Satisfaction of Parents of Children with Autism Spectrum Disorders with the Specialist Support for Child and Family - Anna Monika Gagat-Matuła; Tomasz Gosztyła; Aneta Lew-Koralewicz; Izabela Marczykowska (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: There is a significant increase in the number of children and adolescents diagnosed with autism spectrum disorder (ASD). The principle of collaboration with parents is one of the basic elements of comprehensive support provided to both children with ASD and their families. Research Aim: The aim of the research was a multi-faceted approach to the level of satisfaction of parents of children with ASD with the professional support and a search for personal traits and dispositions related to the level and various aspects of parents' satisfaction with collaboration with specialists supporting their children and families. Method: The research was carried out in a group of 204 parents of children with ASD. The following measures were used: Family-Professional Partnership Scale (FPPS), Enabling Practices Scale (EPS), Ten Item Personality Inventory (TIPI) - TIPI-PL; Psychological Entitlement Scale (PES), and Gratitude Questionnaire (GQ-6). Results: The obtained results show an above-average satisfaction of parents with the support they receive. Significant predictors of the satisfaction of surveyed parents with the specialist support were the following personal characteristics and dispositions: gratitude, agreeableness, conscientiousness and openness. Conclusions: The results enable an initial assessment of satisfaction with formal support among parents of children with ASD. They also indicate selected personal dispositions related to a high level of satisfaction with the support received.